ANALYSIS OF FINANCIAL PERFORMANCE OF MINING COMPANIES LISTED IN INDONESIA STOCK EXCHANGE - Prabowo, Satriya Candra Bondan; Korsakul, Nattawadee (Jurnal Aplikasi Manajemen, 2020)
This study aims to determine and analyze the financial performance of mining companies listed on the Indonesia Stock Exchange. The objects taken in this research were 37 mining companies listed on the Indonesia Stock Exchange during 2013-2017. The results of financial ratio analysis using liquidity ratios, activity ratios, solvency ratios, profitability ratios and DuPont analysis were fluctuating, shown by the increase and decrease in most mining companies during the research period. The higher the liquidity ratio, the higher the safety level of the company and vice versa. The higher the activity ratio, the higher the efficiency of the company and vice versa. A high solvency ratio is not good for the company because the loan will be greater, so the risk will be greater as well and vice versa. The higher the profitability ratio, the better the operating conditions of the company in generating profits and vice versa. Based on DuPont analysis, great ROI and ROE is good for the company because its management in assetsthat generate operating profit will be better too.